Hormonal bases of growth and yield in tomato (Solanum lycopersicum) - Bastos, Carla Elisa Alves (2017)
Tomato hybrids exhibit superior phenotypic performance in both optimal and stressful conditions. This superiority is believed to result from the interaction between the genomes of the parents, altering the transcriptional pattern of genes associated with energy production, metabolic rates, stress responses and hormonal signaling, culminating with higher biomass production and increased yield. QTL analyses indicate that a large number of genes contribute to the heterotic phenotype. The understanding of the physiological bases of heterosis is of interest since it could be targeted by plant breeding programs which can increase yield traits of crops. However, the molecular and physiological mechanisms explaining heterosis are still poorly understood. Therefore, this work was conducted to analyze the hormonal balance of tomato hybrids and to identify the physiological changes that result in the strongest phenotypic and agronomic traits in hybrids plants. The results suggest that the optimization of auxin and ethylene concentrations results in structural changes in leaves and consequently in the photosynthetic assimilation rate, which led to more vigorous vegetative growth of the hybrid plants in to increased fruit production.